A PC based controller system for separately excited dc motors / Nor Azman Abdul Rahman - Abdul Rahman, Nor Azman (1996)
This project is regarding the development of PC based controller system for DC drive application. This system used a personal computer ( PC ) in conjunction with analog and digital, I/O board, a signal sensing and conditioning, subsystem for the acquisition and subsequent processing of current, voltage, and speed signals and a power amplifier module for driving the dc motor. The system improves reliability and performance of dc motor and provides such features as speed control, overload idenfication and protection. The software subsystem is written in the Turbo C and is able to perform the tasks associated with the measurement and control of a dc motor.